Appraisal on the Wound Healing Potential of Deverra tortuosa DC. and Deverra triradiata Hochst Essential Oil Nanoemulsion Topical Preparation - Kamel, Reem A.; Teiama, Mohammed S; El-Hagrassi, Ali M.; Elgayed, Sabah H.; Khattab, Mohamed A.; El-Sayed, Elsayed K.; Ibrahim, Magda T.; Mady, Mohamed S.; Moharram, Fatma A. (Frontiers in Pharmacology, 2022)
Deverra tortuosa (Desf.) DC. and Deverra. triradiata Hochst. ex Bioss are perennial desert shrubs widely used traditionally for many purposes and they are characteristic for their essential oil. The objective of the present study was to investigate the in vivo wound healing activity of the essential oil (EO) of D. tortuosa and D. triradiata through their encapsulation into nanoemulsion. EO nanoemulsion was prepared using an aqueous phase titration method as well as, nanoemulsion zones were identified through the construction of phase diagrams. The EO was prepared by hydrodistillation (HD), microwave-assisted hydro-distillation (MAHD), and supercritical fluid extraction (SFE) and analyzed using GC/ MS. D. tortuosa oil is rich in non-oxygenated compound, representing 74.54, 73.02, 41.19 in HD, MADH, and SFE respectively and sabinene represents the major monoterpene hydrocarbons. Moreover, D. triradiata is rich in oxygenated compounds being 69.77, 52.87, and 61.69 percent in HD, MADH, and SFE respectively with elemicin and myristicin as major phenylpropanoids. Topical application of the nanoemulsion of D. tortuosa and D. triradiata (1% or 2%) exhibited nearly 100% wound contraction and complete healing at day 16 Moreover, they exhibit significant antioxidant, and anti-inflammatory effects and, a significant increase in growth factors and hydroxyproline levels. Histopathological examination exhibited complete re-epithelialization accompanied by activated hair follicles and abundant collagen fibers, especially at a concentration of 2%. Therefore, the incorporation of the two Deverra species in nanoemulsion could professionally endorse different stages of wound healing.